Advancing the Modern Urban Manifestation of Harmonious Coexistence between Humans and Nature: Illustrated by the Construction of Chengdu Park City in China - Yang, Can (International Journal of Social Sciences and Public Administration, 2024)
In the report of the 20th National Congress of the Communist Party of China, the harmonious coexistence between humanity and nature was established as a key development objective and a defining feature of China’s path to modernization. Consequently, promoting the expression of modern cities that embody this harmonious coexistence is integral to advancing China’s unique modernization drive. This paper delves into the genesis of the concept of modernization centered on the harmonious coexistence of humanity and nature. It examines the historical, theoretical, and practical linkages between this coexistence and China’s modernization efforts. Furthermore, taking the construction of the Chengdu Park City Demonstration Area as a case study, the paper unpacks the expression of a modern city that embodies the harmonious coexistence of humanity and nature. By comprehensively exploring the concept’s genesis, policy agendas, mission objectives, and construction achievements, this paper offers a comprehensive overview of Chengdu’s park city construction. It analyzes the practical logic and significance of Chengdu’s park city from the perspective of harmonious coexistence between humans and nature, ultimately demonstrating that park city construction serves as a modern urban expression of this harmonious coexistence.